Waveguide grating couplers with bandwidth beyond 200 nm - Zhou Xuetong; Xue Ying; Feng Hanke; He Jianfeng; Sun Xiankai; Wang Cheng; Lau Kei May; Tsang Hon Ki (Nanophotonics)
We propose and validate a new approach for wideband waveguide grating couplers (GC). The wideband operation is achieved using a slot waveguide grating structure above the conventional channel waveguide. With this slot waveguide grating structure, both the grating strength, mode effective index and dispersion in the grating region can be flexibly tuned to enable high coupling efficiency and wideband operation. 3D FDTD simulations predicted coupling efficiency of −4.08 dB with unprecedented 1 dB bandwidth of 229 nm. The experimental result in coupling with standard single mode fiber in the C band to a lithium niobate waveguide achieved −4.47 dB coupling efficiency with 1 dB bandwidth of 171 nm and 3 dB bandwidth of over 200 nm. The unprecedented wide optical bandwidth is achieved without using bottom metal reflectors or the etching of grating structures on the lithium niobate material.